Pergulatan Sejarah dan Isu-Isu Kontemporer dalam Wacana Otoritas Hadits - Jailani, Mohammad (Jurnal Moderasi, 2022)
The realm of hadith has evolved and expanded to encompass not only the term "hadith" but also "sunnah," "khabar," and "atsar." These four terms, while sharing some similarities, also hold distinct meanings. It is crucial to clarify their significance within each context to avoid confusion and misinterpretation. Hadith, as a concept, contains al-Khabar (information) derived from the al-Kalam (sayings) of the Prophet, which is jadid (new) when compared to al-Kalam of Allah (the Quran). On the other hand, "sunnah" denotes the way, method, or path. Originally, it referred to the path established and followed by previous generations, becoming a guiding route for those who follow. Scholars from different disciplines define hadith in alignment with their specific scientific fields. For instance, Ushul fiqh experts identify sunnah as everything derived from the Prophet (apart from the Quran), including words, deeds, and provisions that serve as justifications for Syara` law. Reviewing hadith and its miraculous aspects becomes essential to counter erroneous perceptions and logically demonstrate its miracles. In the contemporary era, the study of hadith and sunnah not only emphasizes the quality of narrators but also the quantity to foster a comprehensive understanding. This abstract seeks to shed light on the terminological nuances of hadith, sunnah, khabar, and atsar, ensuring clarity and precision in their interpretations. Furthermore, it highlights the significance of examining the miraculous aspects of hadith and its relevance in contemporary scholarship, providing a holistic perspective that enriches the understanding of these essential sources of Islamic guidance.